An Investigation of Some Macro-Financial Linkages of Securitization - Long, Xin (IMF Working Papers; Working Paper ;, 2009)
Policy-makers have attributed the scale of the credit crisis and its profound impact on money markets (as well as financial sector stability) to the fast rise of securitization and the way it has arguably complicated both the conduct of monetary policy and the effect of interest rate transmission to the real economy. In our study, we examine whether financial innovation, specifically through securitization, has altered the nature of some macro-financial linkages, often with considerable policy implications. We find that securitization activity in the United States (mature market) and South Africa (emerging market) has indeed dampened the interest rate elasticity of real output via the balance sheet channel (while decreasing the interest rate pass-through from policy rates to market rates). That being said, current reservations about securitization do not invalidate the fact that securitization activity helps cushion the immediate impact of interest rate shocks to loan origination, which might be particularly effective in EM countries where poorly developed capital markets provide few alternatives to bank lending.